2016
DOI: 10.3390/rs8030226
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Influence of Seasonality, Condition, and Species Composition on Mangrove Leaf Pigment Contents and Laboratory Based Spectroscopy Data

Abstract: Abstract:The purpose of this investigation was to determine the seasonal relationships (dry vs. rainy) between reflectance (400-1000 nm) and leaf pigment contents (chlorophyll-a (chl-a), chlorophyll-b (chl-b), total carotenoids (tcar), chlorophyll a/b ratio) in three mangrove species (Avicennia germinans (A. germinans), Laguncularia racemosa (L. racemosa), and Rhizophora mangle (R. mangle)) according to their condition (stressed vs. healthy). Based on a sample of 360 leaves taken from a semi-arid forest of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 69 publications
1
20
0
3
Order By: Relevance
“…Flores-de-Santiago et al [15] analyzed the relationship between leaf reflectance and pigments, chlorophylls and carotenoid, in three mangrove species in order to assess their health condition. 360 leaves collected from a semi-arid forest of the Mexican Pacific showed the highest maximum correlations at green and red-edge bands for chl-a and chl-b.…”
Section: Highlights Of Research Articlesmentioning
confidence: 99%
“…Flores-de-Santiago et al [15] analyzed the relationship between leaf reflectance and pigments, chlorophylls and carotenoid, in three mangrove species in order to assess their health condition. 360 leaves collected from a semi-arid forest of the Mexican Pacific showed the highest maximum correlations at green and red-edge bands for chl-a and chl-b.…”
Section: Highlights Of Research Articlesmentioning
confidence: 99%
“…After applying analysis of variance to hyperspectral data collected from mangrove leaves under laboratory conditions, Vaiphasa et al identified sixteen mangrove species [22]. The chlorophyll content has also been used to indicate how oil pollution and seasonal stress to mangroves [23,24]. Flores-de-Santiago estimated the chlorophyll content in mangroves in different seasons from hyperspectral data to determine the optimal time for monitoring [25].…”
mentioning
confidence: 99%
“…Curran obtained the optimal red-edge band for estimating the chlorophyll content by establishing a relationship between the red-edge position and reflectivity at different wavelengths [38]. Flores-de-Santiago and Zhang et al suggested that wavebands at the red edge position were the best predictors of the pigment contents [24,39].Hyperspectral remote sensing has been used successfully to monitor the restoration of ecosystems; for example, vegetation abundance and vegetation succession inversion during restoration [9,40,41], and inverted vegetation physicochemical indexes [31,35,42]. Further, previous studies have mostly concentrated on farmland economic crops and there have been few studies of coastal wetland plants [43].…”
mentioning
confidence: 99%
See 2 more Smart Citations